Masyarakat dan kebudayaan Cina - Gondomono, Gondomono (UI Scholars Hub, 2002)
This paper attempts to trace the identity construction of the Chinese from cultural anthropology perspective. It argues that the constructed identity is always changing and very much influenced by socio, economic, political and cultural aspects. By looking at the society, the language, the kinship and belief system, it comes to a conclusion that the identity is not as simple as it looks. In fact, it often embodies a misperception of what it this to be Chinese. In this context, emphasises the needs for further development of Chinese studies in Indonesian universities.